Dryout modelling for both homogeneous and stratified debris beds - Peng, Cheng; Shi, Kaiwen; Deng, Jian; Wu, Jiang (Frontiers in Nuclear Engineering, 2025)
IntroductionDuring severe accidents, the interaction of hot melt with coolant forms porous debris beds in the reactor lower head or cavity. The long-term coolability of these beds is critical for accident mitigation and reactor safety enhancement, primarily determined by the dryout heat flux (DHF). Despite existing models, gaps persist in accounting for two-phase flow dynamics and interfacial shear effects.MethodsThis study develops high-fidelity mechanistic models to address these limitations. First, classical DHF models are reviewed, identifying key assumptions requiring refinement. New models are derived by incorporating: (1) two-phase flow characteristics (e.g., relative permeability, capillary pressure) and (2) gas-liquid interfacial shear stress. These models are extended to stratified debris bed configurations. Validation is performed using experimental data from KTH's POMECO-HT (top-injection) and VTT's STYX-3.1 tests.ResultsThe two-phase flow model achieved a 20% DHF prediction error, while the interfacial shear model reduced errors to 8.9%. For stratified beds, the error further decreased to 4.5%, demonstrating superior accuracy.DiscussionThe results highlight the necessity of interfacial shear effects and stratification in DHF predictions. The proposed models offer a robust foundation for debris bed cooling analysis codes, significantly improving safety assessments.